A new energy system based on biomass gasification for hydrogen and power production - H. Ishaq; Ibrahim Dincer (Energy Reports, 2020)
In this paper, a new gasification system is developed for the three useful outputs of electricity, heat and hydrogen and reported for practical energy applications. The study also investigates the composition of syngas leaving biomass gasifier. The composition of syngas is represented by the fractions of hydrogen, carbon dioxide, carbon monoxide and water. The integrated energy system comprises of an entrained flow gasifier, a Cryogenic Air Separation (CAS) unit, a double-stage Rankine cycle, Water Gas Shift Reactor (WGSR), a combined gas-steam power cycle and a Proton Exchange Membrane (PEM) electrolyzer. The whole integrated system is modeled in the Aspen plus 9.0 excluding the PEM electrolyzer which is modeled in Engineering Equation Solver (EES). A comprehensive parametric investigation is conducted by varying numerous parameters like biomass flow rate, steam flow rate, air input flow rate, combustion reactor temperature, and power supplied to the electrolyzer. The system is designed in a way to supply the power produced by the steam Rankine cycle to the PEM electrolyzer for hydrogen production. The overall energy efficiency is obtained to be 53.7% where the exergy efficiency is found to be 45.5%. Furthermore, the effect of the biomass flow rate is investigated on the various system operational parameters.
Keywords: 330; Biomass gasification; Hydrogen production; PEM electrolyzer; Cryogenic air separation unit; Power production; Efficiency